Development of evidence-based Australian medication-related indicators of potentially preventable hospitalisations: a modified RAND appropriateness method - Caughey, Gillian E (BMJ Publishing Group, 2014)
OBJECTIVE: Indicators of potentially preventable hospitalisations have been adopted internationally as a measure of health system performance; however, few assess appropriate processes of care around medication use, that if followed may prevent hospitalisation. The aim of this study was to develop and validate evidence-based medication-related indicators of potentially preventable hospitalisations. SETTING: Australian primary healthcare. PARTICIPANTS: Medical specialists, general practitioners and pharmacists. A modified RAND appropriateness method was used for the development of medication-related indicators of potentially preventable hospitalisations, which included a literature review, assessment of the strength of the supporting evidence base, an initial face and content validity by an expert panel, followed by an independent assessment of indicators by an expert clinical panel across various disciplines, using an online survey. PRIMARY OUTCOME MEASURE: Analysis of ratings was performed on the four key elements of preventability; the medication-related problem must be recognisable, the adverse outcomes foreseeable and the causes and outcomes identifiable and controllable. RESULTS: A total of 48 potential indicators across all major disease groupings were developed based on level III evidence or greater, that were independently assessed by 78 expert clinicians (22.1% response rate). The expert panel considered 29 of these (60.4%) sufficiently valid. Of these, 21 (72.4%) were based on level I evidence. CONCLUSIONS: This study provides a set of face and content validated indicators of medication-related potentially preventable hospitalisations, linking suboptimal processes of care and medication use with subsequent hospitalisation. Further analysis is required to establish operational validity in a population-based sample, using an administrative health database. Implementation of these indicators within routine monitoring of healthcare systems will highlight those conditions where hospitalisations could potentially be avoided through improved medication management.